PHYTOCHEMISTRY AND PHARMACOLOGY OF PTEROCARPUS SANTALINUS AND ITS ROLE IN DERMATOLOGY - KUCHEKAR, MOHINI; NAVGHARE, VIJAY; KULKARNI, AMRITA; ZAMBARE, AISHWARYA; CHOUDHARY, BHARTI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
The review provides an updated overview of the phytochemical and pharmacological studies on Pterocarpus santalinus. It briefs on the synergistic interactions of P. santalinus with other medicinal plants and its use in Ayurvedic formulations. Phytochemical analysis suggests the presence of triterpenoids, steroids, flavonoids, and phenolic acids. The phytoconstituents and related pharmacological activities of various parts of P. santalinus include antifungal, anticholinesterase, antidiabetic, antibacterial, antipyretic, anti-inflammatory, anticancer, and antiulcer. Literature survey highlights the dermatological applications of the phytoconstituents such as pterostilbene, savinin, and betulin as potential leads for anti-aging, ultraviolet rays (UV-B) protective, and wound healing effects. Undoubtedly, P. santalinus has wide therapeutic value. The dermatologically significant phytoconstituents, namely, pterostilbene, cedrol, savinin, lupeol, betulin, β-eudesmol, and α-bisabolol, if isolated and used in dermatological formulations, can show promising skin protective effect. The data were compiled using scientific databases, namely, Google Scholar and PubMed, the data made available specifically from 2010 to 2021.